2020
DOI: 10.1590/1809-4392202000302
|View full text |Cite
|
Sign up to set email alerts
|

Effect of density of fingerling and juvenile pirarucu during transportation on water quality and physiological parameters

Abstract: We assessed the effect of stocking density on physiological parameters (blood lactate, glucose, cortisol, hematocrit), water quality (temperature, dissolved oxygen, pH, unionized ammonia, carbon dioxide), and survival during the transportation of fingerling (24.5 ± 4.7 g) and juvenile (615.8 ± 122.2 g) pirarucu (Arapaima gigas) for six hours in plastic bags. The tested densities were 65, 80, 95, 110 and 125 g L-1 for fingerlings, and 50, 80, 110, 140 and 170 g L-1 for juveniles (three replicates each). Paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Methods such as ice cooling are often used to reduce water temperature during live transport [ 45 ], and these are similarly noted in the current study - the reported addition of ice into water. Lower water temperatures can also help to maintain water quality during transport [ 9 ]. For example, in a previous study, ammonia nitrogen concentrations were lower when largemouth bronze gudgeons ( Coreius guichenoti ) were transported in cool water [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods such as ice cooling are often used to reduce water temperature during live transport [ 45 ], and these are similarly noted in the current study - the reported addition of ice into water. Lower water temperatures can also help to maintain water quality during transport [ 9 ]. For example, in a previous study, ammonia nitrogen concentrations were lower when largemouth bronze gudgeons ( Coreius guichenoti ) were transported in cool water [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Live transport includes pre-transport procedures (grading, crowding, netting, fasting, handling, and loading/packing), during transport procedures, and post-transport processes (unloading and handling), which are potentially stressful to fish [ 6 , 7 ]. Common stressors associated with live transport are inappropriate handling, air exposure, food deprivation, poor water quality, inappropriate transport densities, sudden changes in water temperature, and rapid water movement [ 3 , 5 , 8 , 9 , 10 ]. It is challenging to maintain the health and well-being of live fish during transport, particularly because of the large numbers of animals in many varied transport situations.…”
Section: Introductionmentioning
confidence: 99%
“…The plasma glucose of pirarucu was higher at the AT moment and followed by a reduction in the 24 h time, stabilizing in the 48 h time, suggesting the effect of secondary stress triggered at the moment AT. Lima et al (2020) also observed a significant increase in pirarucu glucose AT in all treatments, returning to baseline levels during the recovery period. Change in plasma glucose is a physiological response in many fish species and may increase or decrease, or remain constant after an increase in plasma cortisol (Mommsen et al, 1999).…”
Section: Discussionmentioning
confidence: 78%
“…In larger pirarucu (9 kg), as the stocking density increased during transport, the hematocrit increased with rising time (Lima & de Oliveira, 2017). In pirarucu juveniles (615.8 g), testing was done for transport in plastic bags and different densities, and the hematocrit was significantly lower AT at a density of up to 140 g L À1 (Lima et al, 2020), showing that this secondary stress indicator varies according to the intensity of the stress suffered (Sampaio & Freire, 2016), and adequate transport can minimize stress during this management, while high fish density is important to reduce costs (de Abreu et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation